Penerapan Algoritma Regresi Linier Berganda dalam Mengestimasi Jumlah Perceraian di Pengadilan Agama Simalungun - Samosir, Rafiah Aini; Rozy, Muhammad Fachrur; Windarto, Agus Perdana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The number of divorces each year continues to increase, including what is happening at the Simalungun Religious Court. Divorce by the male party is called divorce talak and that is done by the woman and is called divorce suicidal. There are many aspects that cause divorce every year. With the continuing increase in the divorce rate that is happening, employees who work must carry out their work as effectively as possible. This study aims to recommend estimating the number of divorces in the Simalungun religious court. Researchers use the method of applying data mining multiple linear regression algorithms. The source of this research data was obtained by means of interviews and direct observation to the secretariat in the Simalungun religious court